2017
DOI: 10.1021/acsami.7b00136
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Three-Stage Switching of Wetting, Morphology, and Protein Adsorption

Abstract: The novel polymeric coatings of oligoperoxide-graft-poly(4-vinylpyridine-co-oligo(ethylene glycol)ethyl ether methacrylate246) [oligoperoxide-graft-P(4VP-co-OEGMA246)] attached to glass were successfully fabricated. The composition, thickness, morphology, and wettability of resulting coatings were analyzed using X-ray photoelectron spectroscopy, ellipsometry, atomic force microscopy, and contact angle measurements, respectively. In addition, adsorption of the bovine serum albumin was examined with fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 59 publications
1
20
1
Order By: Relevance
“…Carbon C1s spectra were fitted with three peeks corresponding to C-C (284.8 eV) C-O or C-N (286.5 eV) and O-C=O (288.5 eV) bonds. The peak positions are only slightly different from those determined for "pure" POEGMA and presented in our earlier work [62]. In addition, the relative intensities of the peaks vary slightly from those previously measured.…”
Section: Resultscontrasting
confidence: 82%
“…Carbon C1s spectra were fitted with three peeks corresponding to C-C (284.8 eV) C-O or C-N (286.5 eV) and O-C=O (288.5 eV) bonds. The peak positions are only slightly different from those determined for "pure" POEGMA and presented in our earlier work [62]. In addition, the relative intensities of the peaks vary slightly from those previously measured.…”
Section: Resultscontrasting
confidence: 82%
“…It was also shown that the hydrodynamic radius of these systems decreased two-fold at around 32 • C (Figure 5c). In addition, BNNTs were functionalized by other grafted polymer brushes, similar to other works [91,92].…”
Section: Boron Nitride Nanotubesmentioning
confidence: 86%
“…The phase of the samples were characterized by X-ray diffraction patterns. It is noted that the growth conditions will affect the morphology and thus the magnetic properties of the prepared samples [29][30][31][32]. In order to investigate this effect, experiment under different growth conditions were executed.…”
Section: Resultsmentioning
confidence: 99%